INVESTIGATION OF PARAMETERS OF TECHNOLOGICAL PROCESS OF ENRICHMENT OF LOW-NICKEL DEAD CATALYST - O. S. Komarov; D. O. Komarov; V. I. Volosatikov; I. E. Provorova (Литьë и металлургия)
The influence of parameters of the technological process on proportion of Al and Ni in nickel concentrate, received on the basis of used catalyst with low content of nickel is studied.